(untitled) (Nigerian Journal of Physiological Sciences, 2022)
The effect of virgin coconut oil (VCO) supplemented diet on sodium benzoate (SB) – induced neurotoxicity in male Wistar rats was investigated. Twenty (20) male Wistar rats weighing 160-180g were divided into four (4) groups: Control which received 1ml of normal saline, SB-treated; received 200 mg/kg b.w, SB + Low Dose VCO-treated (SB + 5% VCO mixed with 95g of rat chow), and SB + High Dose VCO-treated (SB+ 15% VCO mixed with 85g of rat chow). The brain was processed for NRF-2, NF-kB, and acetylcholine esterase (AchE) gene expression levels. Also, the blood sample was processed for assessment of superoxide dismutase (SOD), catalase (CAT), and IL1B levels. One-way ANOVA and Tukey post hoc tests were used to analyze data. SB-treated rats with no intervention showed anxiety-like behavior and impaired memory as depicted by a significant (p<0.0001) increase in anxiety index, increase in brain NF-KB, increase in serum IL1B and increase in AchE gene expression level, reduction in the recognition ratio, decreased spontaneous alternation performance, decreased CAT and SOD levels and decreased NRF-2 expression level when compared to other groups (especially control and SB + 5% VCO). VCO supplemented diet (both 5% and 15%) significantly (p<0.0001) increased the CAT and SOD levels, increased the NRF-2 gene expression level, and significantly (p <0.0001) decreased the IL1-B level. Moreover, 5% VCO significantly (p<0.0001) decreased the anxiety index, decreased AchE and NFkB gene expression levels, increased spontaneous alternation performance, and increased recognition ratio compared to 15% VCO. VCO shows a neuroprotective effect in attenuating cognitive impairment and anxiety-like behavior in SB-induced model by modulating oxidative stress and inflammatory pathways, and also enhancing cholinergic neurotransmission. Keywords: Virgin coconut oil; sodium benzoate; acetylcholinesterase; catalase; superoxide dismutase; oxidative stress